Pengelolaan Penerimaan Peserta Didik Baru (PPDB) Ditinjau Dari Perspektif Total Quality Management (TQM) di Madrasah Bertaraf Internasional (MBI) Amanatul Ummah Pacet Mojokerto - Al Qorony, Wais; Mujiono (Menara Tebuireng, 2024)
Abstract— Educational institutions prioritize quality. With the emergence of competing schools, it becomes very important to identify schools that meet quality standards. The TQM integrated quality control system combines the efforts of developing, maintaining, and improving quality from all levels in an organizational group to increase productivity levels. To become a learner at an educational institution (madrasah), there must be registration of new learners, first a search process is carried out, then a recruitment process is carried out to identify prospective new learners and capture these prospective learners. The purpose of this research has been adjusted to the focus of the research, so that it is an effort to provide a comprehensive explanation and description: 1) To analyze the selection process of new student admissions at MBI Amanatul Ummah. 2) To analyze the implications of the selection process of new student admissions at MBI Amanatul Ummah. This research is a field study with a qualitative approach applied. In this study, various data collection techniques were used by researchers through the Observation method, Interview Method, Documentation Method. The results showed the results that 1) PPDb program planning at MBI Amanatul Ummah in its implementation, MBI leaders wait for direction from the foundation. 2) The PPDb committee is taken from the Functionalists, TU Staff, and Head of Class. The information media used are social media and the school website. 3) The tests tested in the written test path are academic potential tests and psychological tests. The achievement path is opened only for those who have a minimum certificate of district level champion, the test tested is an interview related to the certificate attached. Key Words: Total Quality Management, New Student Registration